PERAN LEMBAGA ADAT MELAYU RIAU ROKAN HULU DALAM PROSES PENYELESAIAN SENGKETA KEBUN PERSUKUAN MELAYU TAMBUSAI KUALA MAHATO DENGAN PT. TORUSGANDA DI KABUPATEN ROKAN HULU - Irma Nora; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Unalienated land land use indigenous Malay Tambusai Kuala persukuan Mahato with company Torusganda began to trigger problems arising from the existence of the discrepancy of the results obtained by indigenous peoples with the contents of the cooperation agreement created by both sides. Because it cannot solve the problem at the village level to make indigenous peoples requesting assistance to Indigenous Institutions of Rokan Hulu, Riau Malay as the container to get the legal protection over customary rights. So the role of Adat Melayu Riau Rokan Hulu becomes important to review considering rules governing the functioning of the institutions of Riau Malay custom Rokan Hulu is still described in General. Indigenous institutions in this case has a great opportunity to be the place or means in resolving disputes in non litigation.Interest thesis writer namely; First, to know the role of Rokan Hulu, Riau Malay Customs in the dispute resolution process of garden persukuan Malay tambusai kuala mahato with PT. Torusganda in the Rokan Hulu; Second, to know the constraints of Riau Malay Customs Institutions of Rokan Hulu in the dispute resolution process of garden persukuan Malay tambusai kuala mahato with PT. Torusganda in the Rokan Hulu. Types of legal research that used the author is kind of juridical sociological research. A legal sociological research or empirical research, this is the type of research objectives of the law. From the results of research, there are two things which can be inferred. First, the Riau Malay Customs Institutions of Rokan Hulu does not yet have the authority to say clearly in the position of the mechanism in resolving disputes of indigenous issues. The form of seriousness in defending the interests of indigenous rights related customary land is still not published by the Government so that the position of indigenous institutions in solving plantation Malays Kuala Tambusai Mahato as just the mediator, judge and could not decide. The position of the indigenous institution still governed in General and customary institutions make extensive has not been able to resolveJOM Fakultas Hukum Volume V Edisi 2 Juli-Desember 2018 2this issue in totality. Second, Constraints that occurred in the settlement of problems of plantation persukuan Melayu Kuala Tambusai Mahato conducted by LAMR Rokan Hulu is influenced by two factors, namely the internal factors and external factors. These factors greatly affect the performance of members of the indigenous institutions in carrying out its work. So the constraint triggers the lack of existence of indigenous institutions to protect the rights of indigenous peoples recognized constitutionally.Keywords: Indigenous Institutions – Customary Land – Settlement of disputes